UTILIZATION OF BIM (BUILDING INFORMATION MODELING) TECHNOLOGY TO INCREASE EFFICIENCY AND ACCURACY OF INFRASTRUCTURE PROJECT PLANNING - Tomi Apra Santosa (LPPM Akademi Teknik Adikarya, 2024)
This research aims to investigate the use of BIM (Building Information Modeling) Technology as an innovative solution in increasing the efficiency and accuracy of infrastructure project planning. The research method consists of identifying stakeholder needs, developing an integrated 3D BIM model, validating and testing the model, integration into the Project Information Management System (PMIS), as well as training and application in the field. By adopting this approach, it is hoped that it will be able to improve the quality of planning information, provide a holistic view of the project, and optimize collaboration between stakeholders. This research focuses not only on the technical aspects of BIM models, but also on their practical implementation in real construction environments. The results of this research are expected to make a significant contribution to increasing the effectiveness of infrastructure project management through the use of BIM technology.